Topical Anesthesia for Cataract Surgery: The Patients' Perspective. (23rd June 2014) - Apil, Aytekin; Kartal, Baki; Ekinci, Metin; Cagatay, Halil Huseyin; Keles, Sadullah; Ceylan, Erdinc; Cakici, Ozgur
Abstract : Purpose . To evaluate the analgesic efficacy of 0.5% propacaine hydrochloride as topical anesthesia during phacoemulsification surgery. Methods . Intraoperative pain intensity was assessed using a 5-category verbal rating scale during each of three surgical stages. Pain scores from each surgical stage and total pain scores were compared for the factors of patient age, gender, cataract laterality, and type. Results . In comparison of cataract type subgroups, the mean total pain scores and mean stage 2 pain scores in both white mature cataract (WMC) and corticonuclear plus posterior subcapsular cataract (CN + PSC) groups were significantly higher than in the PSC-only (PSC) groupP < 0.05 . Conclusion . Phacoemulsification with topical anesthesia is not a completely painless procedure. Pain intensity varies with cataract type and stage of surgery.